Antioxidants and cisplatin nephrotoxicity; an updated review on current knowledge - Ramin Tolouian; Audrey Tolouian; Farzaneh Dastan; Vida Farhangi; Payam Peymani; Sanam Saeifar; Oscar Felipe Borja Montes; Leila Mohmoodnia; Mohammadreza Khosravifarsani; Tella Sadighpour (Society of Diabetic Nephropathy Prevention, 2023)
Cisplatin is a first-line antitumor drug which is applied in the therapeutic field of numerous kinds of cancers. The main dose-dependent adverse effect of cisplatin is nephrotoxicity in approximately one-third of patients, who received this drug during their treatment. Oxidative stress is one of the most significant mechanisms in cisplatin nephrotoxicity. Cisplatin-induced oxidative stress stimulates apoptosis, inflammation, mitochondrial damage within cells, and endoplasmic reticulum (ER) stress. The administration of an antioxidant in this context could be a suitable approach for preventing of cisplatin nephrotoxicity. Antioxidants are categorized into four classes: dietary antioxidants, free radical scavengers, thiol-containing compounds, and iron chelators.